EFFECT OF FEED COMPOSITION ON SPONSTIC PLASTIC WASTE DEGRADATION, SURVIVALITY AND LARVA GROWTH Tenebrio molitor L. - Wachju Subchan; Lintang Mutiara Putri; Dwi Wahyuni; Sugeng Winarso (BIOEDUKASI, 2022)
Sponge plastic is one of the plastic wastes that is difficult to degrade. Recently research reported that Tenebrio molitor L larvae have the potential capability to degrade plastic waste. But still a lack information according to the effect of feed composition on survival, and growth of T. molitor L larvae. The purpose of this study was to determine the effect of plastic feed composition on the rate of degradation of sponge plastic waste, survival, and growth of T. molitor L larvae. The method used in this study was an experimental laboratory using Completely Randomized Design (CRD) and using controls and six treatments with 3 repetition times. The parameters measured in this study were survival (%), body length growth (cm/week) and body biomass (gram/week), and degradation rate (gram/week). The data obtained from the research results will be analyzed using ANOVA which is then tested by Duncan. The results showed that feed composition had a significant effect (p=0.001) on the rate of degradation of plastic sponge waste, survival (p=0.000), and growth (p=0.001) of T. molitor L larvae. degradation, survival, and growth of T. molitor L. larvae.